Povezanost različitih indeksa disfunkcije koronarne mikrocirkulacije sa veličinom infarkta nakon primarne perkutane koronarne intervencije: Coronary microvascular dysfunction and infarct size - Milašinović, Dejan (Medical Research, 2025)
Introduction: Coronary microvascular dysfunction (CMD) has been associated with impaired prognosis in patients with ST-elevation myocardial infarction (STEMI) despite timely and successful primary percutaneous coronary intervention (PCI). Our aim was to compare the ability of two different CMD indices, coronary flow reserve (CFR) and hyperemic microvascular resistance (HMR), to predict infarct size. Methods: The analysis included 31 patients with STEMI in whom valid invasive measurements of coronary blood flow velocity with the Doppler-tipped coronary wire, had been performed at the end of primary PCI, and in whom infarct size was determined by cardiac magnetic resonance (CMR) after at least 3 months. Receiver operating (ROC) curves were used to comparatively assess the capacity of HMR and CFR to predict large infarction, defined as the highest quartile of the included population (≥16% of the left ventricular mass). Results: Invasive measurements at the end of primary PCI revealed average HMR value of 2.72±0.86 mmHg/cm/s, and that of CFR to be 1.65± 0.36. Both indices of microvascular function significantly correlated with infarct size (rho=0.569, p
Keywords: coronary microcirculation, infarct size, primary PCI.